Aqueous proton-selective conduction across two-dimensional graphyne - Le Shi (Nature Portfolio, 2019)
Aqueous proton-selective membranes are vital for methanol fuel cells and flow batteries, but suffer from crossover issues. Here the authors use ab initio molecular dynamics simulations to show that graphyne is an ideal candidate for a proton-selective membrane that can be tailored for methanol impermeability